TDS (TOTAL DISSOLVED SOLIDS) SENSOR IMPLEMENTATION FOR AUTOMATIC WATER CONTROL IN HYDROPONIC PLANTS - Pratama, Aditya Nanda; Rasmana, Susijanto Tri; Triwidyastuti, Yosefine (Journal of Control and Network Systems (JCONES), 2017)
Hydroponics is a technique of planting without using a soil as a growing medium but with the water by tapping on the nutrients requirements of the plant. Treatment methods of hydroponics generally are done by water draining nutrients after the nutrients content of the water decreases with the growth of the plant. Therefore, this study aims to help caring hydroponic plant with control methods of water automatically by using microcontroller. Microcontroller is used to read the data from TDS Sensor and control solenoid valve to control water. From the results of the testing process when the tank is empty and the system will perform filling. After the the tank is full,the system will read the nutritional value. After nutrient density is reduced, the system will perform draining .Based on test results, the system can run optimally and work 100% successfully.